Response of Overwintering Caribou to Burned Habitat in Northwest Alaska - Joly, Kyle; Bente, Peter; Dau, Jim (ARCTIC, 2009)
Caribou (Rangifer tarandus granti) use lichens, when available, as primary forage on their winter range. In boreal forest habitats, wildland fires effectively destroy lichens, and overwintering caribou are known to avoid burned areas for decades while lichen communities regenerate. However, little has been published about caribou response to burned habitat in tundra ecosystems. To assess the relationship between winter caribou distribution and burned areas, we instrumented Western Arctic Herd caribou with satellite telemetry collars and evaluated their locations in relation to recent burns of known age (? 55 years old) across northwestern Alaska. We analyzed caribou distribution for different habitat types (tundra and boreal forest), age categories of burns, and possible edge effects. We also reanalyzed the data, limiting available habitat to a uniform traveling distance (5658 m) from daily satellite locations. Using selection indices that compared caribou use of burns and buffers to their availability, we found that caribou strongly selected against burned areas within the tundra ecosystem. Recent burns were selected against at both large (range-wide) and intermediate (5658 m) spatial scales. Caribou particularly selected against 26- to 55-year-old burns and the interior (core) portions of all burns. We found that caribou were more likely to select burned areas in the late fall and early spring than midwinter. Increased fires in northwestern Alaska could decrease the availability and quality of winter habitat available to the herd over the short term (up to 55 years), potentially influencing herd population dynamics and reducing sustainable harvest levels. We recommend that fire managers consider caribou midwinter range condition and extent: however, management that achieves a mosaic pattern of fire history may benefit a wide array of species, including caribou. A better understanding of the current regional fire regime and the distribution of available winter range will be required before practicable ...